Ulama at the Epicenter of the Metropolis The Dialectic of KH. M. Thohir Bakri's Struggle in the Political Currents of Surabaya in the Mid-20th Century - Aditiya, Wildan Ainur (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article analyzes the dialectics of KH. M. Thohir Bakri's struggle within the political landscape of Surabaya as a metropolitan epicenter in the first half of the 20th century. As a young scholar born in the heart of a heterogeneous city, Thohir Bakri represents a synthesis between traditional santri identity and the dynamics of urban movements. This study employs the historical method (heuristics, criticism, interpretation, and historiography) integrated with a sociological approach to dissect the subject's role within the complex social structure of Surabaya. Findings indicate that Thohir Bakri's struggle was an adaptive manifestation of national values, encompassing his roles as the founder and first Chairman of Ansor Nahdlatoel Oelama (ANO), leader of the Surabaya Branch of NU, Chairman of Masyumi Surabaya, and Vice Commander of the Surabaya Hizbullah Army in defending independence. His political career reached a national peak as a member of the Indonesian Constituent Assembly following the 1955 Election. This study concludes that Thohir Bakri successfully navigated the role of a scholar amidst the currents of urban political modernity, establishing him as a significant architect in integrating santri nationalism into the narrative of the national movement in Surabaya.